Hydrophobic fraction of Taenia saginata metacestodes, rather than hydrophilic fraction, contains immunodominant markers for diagnosing human neurocysticercosis Fração hidrofóbica de metacestódeos de Taenia saginata, ao contrário da fração hidrofílica, contém marcadores imunodominantes para o diagnóstico de neurocisticercose humana - Flávia de Assunção Gonçalves; Gleyce Alves Machado; Heliana Batista Oliveira; Maria Teresa Nunes Pacheco Rezende; José Roberto Mineo; Julia Maria Costa-Cruz (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Considering that alternative antigens for diagnosing neurocysticercosis continue to be a challenge because of the increasing difficulty in obtaining parasites from naturally infected pigs for preparation of Taenia solium homologous antigen, the aim of the present study was to evaluate the detergent (D) and aqueous (A) fractions from saline extract of Taenia saginata metacestodes for diagnosing neurocysticercosis. METHODS: Taenia saginata was obtained from naturally infected bovines in the Triângulo Mineiro region, State of Minas Gerais, Brazil. The carcasses came from cold storage units and had been slaughtered in accordance with the inspection technique recommended by the Federal Inspection Service. The D and A fractions were obtained by using Triton X-114 (TX-114). Serum samples were obtained from 40 patients with a diagnosis of neurocysticercosis, 45 with other parasitic diseases and 30 from apparently normal individuals. IgG antibody levels were evaluated using the ELISA and immunoblotting assays. RESULTS: The ELISA sensitivity and specificity were 95% and 73.3%, when using saline extract; 95% and 82.6% for the D fraction; and 65% and 61.3% for the A fraction, respectively. The immunoblotting assay confirmed the ELISA results, such that the D fraction was more efficient than the other extracts, and the 70-68kDa component was immunodominant among neurocysticercosis patients. CONCLUSIONS: These results demonstrated that the D fraction from Taenia saginata metacestodes obtained using TX-114 can be used as a heterologous antigenic fraction in the immunoblotting assay for serologically diagnosing human neurocysticercosis, given its ability to select immunodominant antigens. INTRODUÇÃO: Considerando que antígenos alternativos para o diagnóstico da neurocisticercose (NC) continua sendo um desafio devido ao aumento da dificuldade em se obter parasitas de suínos naturalmente infectados, para a preparação do antígeno homólogo de Taenia solium, o objetivo do presente estudo foi avaliar frações detergente (D) e aquosa (A), do extrato salino de metacestódeo de Taenia saginata para diagnóstico da NC. MÉTODOS: Bovinos, naturalmente infectados com Taenia saginata, procedentes da região do Triângulo Mineiro, Estado de Minas Gerais, Brasil, foram obtidos de frigoríficos e abatidos de acordo com a técnica de inspeção recomendada pelo Serviço de Inspeção Federal. As frações D e A foram obtidas utilizando Triton X-114 (TX-114). Amostras de soro foram obtidas de 40 pacientes com diagnóstico de NC, 45 com diagnóstico de outras doenças parasitárias e 30 de indivíduos aparentemente normais. Níveis de IgG foram avaliados pelos testes ELISA e Imunoblotting. RESULTADOS: A sensibilidade e especificidade do teste ELISA foram 95% e 73,3%, quando utilizado o extrato salino, 95% e 82,6% para fração D, e 65% e 61,3% para a fração A, respectivamente. O ensaio Imunoblotting confirmou os resultados do teste ELISA, sendo a fração D mais eficiente que os outros extratos, observando-se que o componente 70-68kDa se comportou como imunodominante para os pacientes com NC. CONCLUSÕES: Estes resultados demonstraram que a fração D de metacestódeo de Taenia saginata obtida com TX-114 pode ser utilizada como fração antigênica heteróloga pelo Imunoblotting para o diagnóstico sorológico da NC humana, considerando sua habilidade para selecionar antígenos imunodominantes.